Mechanistic Insights of Qingre Jiedu Recipe Based on Network Pharmacology Approach against Heart Failure. (31st January 2022) - Li, Xuan; Shao, Mingyan; Liu, Zhen; Sun, Xiaoqian; Cui, Lingwen; Liu, Xiangning; Wang, Gang; Lu, Linghui; Wu, Yan; Li, Chun
Abstract : Qingre Jiedu (QJ) recipe exerted significant cardioprotective efficacy against heart failure (HF), which is a growing health concern that continues to endanger patients' lives. To investigate the protective properties and mechanism of the QJ recipe, we established hydrogen peroxide (H2 O2 )-induced H9C2 cells and HF rats. The predicted targets and significant pathways of QJ against HF were collected and screened based on network pharmacology from key ingredients and validated by in vivo and in vitro experiments. The decoction of QJ (0.823 g/kg/day) was intragastrically administered for four weeks. QJ (400  μ g/mL) was cultured with H2 O2 stimulated in the H9C2 cells. A total of 31 effective active compounds were screened in QJ and covered 277 targets, of which 85 were shared with HF-related targets. In vivo, the QJ recipe remarkably protected heart function and reduced serum IL-1, IL-6, PIIINP, and CIV levels. Furthermore, QJ downregulated the key proteins mediating inflammatory responses (p-IKK α / β, p-NF κ B, and IL-6) and cardiac fibrosis (STAT3 and MMP-9). In vitro, QJ protected the cardiomyocytes against H2 O2 -stimulated reactive oxygen species (ROS) production and upregulated PI3K and AKT expressions . Further experiments demonstrate that PI3K inhibitor LY294002 remarkably compromised the effects of QJ. In conclusion, our findings indicate that QJ could exert a cardioprotective effect and inhibit fibrosis and inflammation in HF rats via the PI3K-AKT signaling pathway.